2016
DOI: 10.1111/laps.12000
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Economic Statecraft and U.S. Hegemony in Latin America: An Empirical Analysis, 2003–2014

Abstract: If one interprets China's sizable rise in Latin America as an unprecedented phenomenon, it follows that the concurrent story of declining U.S. influence in the region is an event hastily acknowledged at best and ignored at worst. In this article, we ask whether Chinese economic statecraft in Latin America is related to the declining U.S. hegemonic influence in the region and explore how. To do so we analyze foreign direct investments, bank loans, and international trade from 2003 to 2014, when China became a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 57 publications
0
36
1
6
Order By: Relevance
“…Similarly, Urdinez et al [49] find that there is an inverse relationship between the investments made by Chinese SOEs / Chinese bank loans on the one hand, and the US influence in each country on the other hand, suggesting that China is filling a vacuum. This effect of enhanced political closeness between China and its economic partners generates foreign policy consequences, especially for the US which may see China emerge to counterbalance its influence.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Similarly, Urdinez et al [49] find that there is an inverse relationship between the investments made by Chinese SOEs / Chinese bank loans on the one hand, and the US influence in each country on the other hand, suggesting that China is filling a vacuum. This effect of enhanced political closeness between China and its economic partners generates foreign policy consequences, especially for the US which may see China emerge to counterbalance its influence.…”
Section: Literature Reviewmentioning
confidence: 91%
“…If these projects are completed, the China-LA cooperation link will trigger an important change in the global economy, since there will be a stimulation of economic development among developing countries replacing, at the same time, the complete reliance on Western countries from the past (Swaine cited by Hsiang, 2016). The connection between infrastructure projects and the Chinese 'grand strategy' in the region is based on the assumption that Chinese banks and companies reflect the geo-economic strategy given the state intervention and ownership (Urdinez et al, 2016). This assumption is confirmed by data that reports that 81% of the Chinese fdi in LA is performed by State Owned Enterprises (Avendano, Melguizo & Miner, 2017).…”
Section: China In Latin Americamentioning
confidence: 95%
“…From a materialistic view, Keohane defined hegemony as "control over capital, markets and raw materials" (cited by Urdinez et al, 2016). This means that any advance of China in LA in terms of economic agreements, stronger trade relations or large investment projects would undermine Washington's hegemony in the region.…”
Section: China In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Sabatini (, 10), for example, asserts that one of the two primary reasons for the relative decline of influence of the United States in Latin America is the rise of China, and Estep () notes that China has filled the gap left by the lack of U.S. interest in the region. Using sophisticated statistical models Urdinez, Mouron, Schenoni and de Oliveira () found that China strengthened its ties with those countries where U.S. influence was weak . While Ellis () notes that the trend of China's involvement was on the decline in the second semester of 2016, the election of Donald Trump as president of the United States does not bode well for the strengthening of economic ties between the U.S. and Latin America.…”
Section: Has Us Influence Really Declined?mentioning
confidence: 99%